2020
DOI: 10.1016/j.enbuild.2020.109821
|View full text |Cite
|
Sign up to set email alerts
|

Improved day ahead heating demand forecasting by online correction methods

Abstract: To reduce the heating and cooling energy demand of buildings and districts novel control strategies are constantly being developed that require information on the future demand of the controlled entity. Demand forecasting is commonly done with deterministic white box models or fitted grey-box models, however, recently more and more data and machine learning based approaches are being developed. All approaches have weaknesses: white-box models require major modelling effort, grey-box approaches are limited by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 55 publications
(45 reference statements)
1
28
0
Order By: Relevance
“…ML uses several forecasting methods such as Neural Network, Fuzzy Neural Network, Artificial Neural Network, Recurrent Neural Networks, Genetic Algorithm, Support Vector Regression, Random Forest Regressor, Decision Tree Regressor etc. to tackle demand forecasting problems (Abbasimehr et al, 2020;Bünning et al, 2020;Carbonneau et al, 2008;Chang et al, 2009;Chen & Lu, 2017;Claveria et al, 2016;Feng & Wang, 2017;Qiu et al, 2017). Solving demand forecasting problems is not easy because there are many factors that affect demand; one of them is advertisements (Ali et al, 2009;Okrent & MacEwan, 2014;Zheng & Henneberry, 2010).…”
mentioning
confidence: 99%
“…ML uses several forecasting methods such as Neural Network, Fuzzy Neural Network, Artificial Neural Network, Recurrent Neural Networks, Genetic Algorithm, Support Vector Regression, Random Forest Regressor, Decision Tree Regressor etc. to tackle demand forecasting problems (Abbasimehr et al, 2020;Bünning et al, 2020;Carbonneau et al, 2008;Chang et al, 2009;Chen & Lu, 2017;Claveria et al, 2016;Feng & Wang, 2017;Qiu et al, 2017). Solving demand forecasting problems is not easy because there are many factors that affect demand; one of them is advertisements (Ali et al, 2009;Okrent & MacEwan, 2014;Zheng & Henneberry, 2010).…”
mentioning
confidence: 99%
“…Commercial case studies were found applied to offices [72][73][74][75][76][77][78], retail [35], hotels [79], and non-specified (show in references [38,43,45,80]). Focusing on office buildings, it was observed that thermal loads accounted for approximately half of the case studies applied with a predominance of cooling load applications.…”
Section: Commercialmentioning
confidence: 99%
“…DFFNNs have shown promising performance results for forecasting building thermal energy loads. For instance, Bünning et al applied a DFFNN in order to forecast the heating demand of an office building [75]. The model was compared with other prominent black-box and grey-box based models for a forecast horizon of a day-ahead.…”
Section: Commercialmentioning
confidence: 99%
“…To mitigate the problem of high prediction variance between individual networks [37], [38] and [39] propose ensemble methods in the context of building demand prediction. As ensemble methods have the disadvantage of being computationally expensive, we have developed and validated correction methods based on online learning and error autocorrelation correction methods, which both decrease variance and increase accuracy, while avoiding the disadvantages of ensemble methods [40].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we combine the robust MPC for frequency regulation approach presented in [41] with the forecasting methods presented in [40] to offer frequency regulation reserves with a system comprising a ground-source heat pump and water buffer storage that meet the heating demand of a mixed-use building. The robust MPC approach is a further development of [15], which was adapted to this heating system.…”
Section: Introductionmentioning
confidence: 99%